Platinum(II) Complexes of S-Benzyldithiocarbazate based Schiff base ligand: Green synthesis, characterization, cytotoxic and antioxidant assay (Indian Journal of Chemistry (IJC), 2024)
In the present work Benzyl-2-((5-methylthiophen-2-yl)methylene)hydrazine-1-carbothiolate ligand and its platinum(II) complexes were prepared by conventional and microwave assisted methods. Structural elucidation of the ligand and its Pt(II) complexes were performed by elemental analysis, conductance measurements, mass spectrometry, Powder XRD, FT-IR and 1H NMR spectroscopic methods. On the basis of analytical and spectral data, a square planar geometry was suggested for the metal complexes. Starting material(PtCl2), Ligand(LH), metal complexes [Pt(L)2] and [Pt(LH)2]Cl2 were screened for in vitro cytotoxic and antioxidant activity. Cytotoxic activity was performed by MTT[3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] assay against cervical cancer(HeLa) cell line and human breast adenocarcinoma(MCF-7) cell line. Cisplatin was used as the standard drug. [Pt(LH)2]Cl2 complex have shown better cytotoxicity in comparison to ligand and other complex with IC50 values of 72.76 µM and 59.93 µM against HeLa and MCF-7 respectively. The antioxidant activity was measured in terms of radical scavenging ability using the stable radical DPPH. Ascorbic acid was used as positive control and methanol was used as negative control. The ligand was showing excellent antioxidant activity with 70.19 % DPPH inhibition.